2012
DOI: 10.1063/1.4769739
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of MoS2 nanotubes under compression, tension, and torsion from molecular dynamics simulations

Abstract: The mechanical behavior of different types of single-walled and double-walled MoS2 nanotubes when subjected to external compressive, tensile, and torsional loading is investigated using classical molecular dynamics simulations. The forces on the atoms are determined using a reactive empirical bond-order potential parameterized for Mo-S systems. The simulations report on the elastic properties of the different MoS2 nanotube systems as well as the interrelationships between the buckling behavior and the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Ding et al found that the thermal conductivity of SLMoS2 can be effectively tuned by introducing even a small amount of lattice defects, and can be further tuned by mechanical strain [10]. As for MoS2NT, only a few researches focus on the mechanical properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al found that the thermal conductivity of SLMoS2 can be effectively tuned by introducing even a small amount of lattice defects, and can be further tuned by mechanical strain [10]. As for MoS2NT, only a few researches focus on the mechanical properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…A. Elastic approximation model Surface wrinkling has been observed for many multiwalled nanotubes made of carbon 35,[44][45][46][47][48] , boron nitride [49][50][51] , and inorganic materials 52,53 . In those nanomaterials, interaction between adjacent monoatomic lay- ers originates from intermolecular van der Waals (vdW) forces and is thus weak compared with strong chemical bonding 12 .…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Although such single layer nano materials have been investigated using ab initio calculations [12][13][14], molecular dynamics (MD) [15][16][17] and molecular mechanics [18]. There is a limited literature available on the multi layer nano hetero-structures.…”
Section: Introductionmentioning
confidence: 99%